Pelatihan Penggunaan Aplikasi Desain Grafis untuk Meningkatkan Nilai Produk Handmade di PKK Kecamatan Padang Utara - Sri Nita; Popy Maria; Deri Latika Herda; Aprinal Adila Asril; Zidan Pratama Yuda (Warta Pengabdian Andalas, 2024)
The Family Welfare Movement (PKK) of Padang Utara District aims to improve the quality of family life through education, health, and economic development. However, PKK Padang Utara faces challenges in empowering its members, particularly in product promotion in the digital era. The main obstacles are limited digital skills and marketing knowledge. To address these issues, the Community Service (PKM) team from Politeknik Negeri Padang (PNP) provided training in handmade accessories skills and digital marketing using the Canva application. The training methods included lectures, discussions, and practical guidance. The program showed significant skill improvement: 80% of participants experienced increased competency in using Canva for marketing design. In comparison, 100% of participants successfully mastered making handmade accessories. Evaluation of the teaching methods showed the highest satisfaction with practical guidance (100%), followed by discussions (80%) and lectures (50%). This program successfully enhanced individual skills and positively contributed to family economies, enabling PKK Padang Utara to become more independent in facing digital marketing challenges.